Effect of an intensive conservative therapy with daily teriparatide administration and rehabilitation for osteoporotic delayed vertebral collapse and paralysis. Issue 23 (June 2018) - Wakao, Norimitsu; Takeuchi, Mikinobu; Riew, Daniel K.; Hirasawa, Atsuhiko; Imagama, Shiro; Kawanami, Katsuhisa; Matsuo, Toshihiro; Murotani, Kenta; Deie, Masataka
Abstract : Abstract: Although patients with osteoporotic delayed vertebral collapse (ODVC) have frequently been treated surgically, the efficacy and limitation of conservative treatment for it have not yet been reported. The purpose of this study was to investigate the effectiveness and limitation of further intensive conservative treatment for patients with ODVC. Patients treated for ODVC from 2011 to 2014 with a follow-up period of more than 1 year were eligible. The fundamental treatment strategy consisted of surgical treatment following intensive conservative treatment with daily teriparatide and rehabilitation for 3 months. We conducted a surgical treatment for patients who could not keep standing position by themselves because of prolonged leg paralysis or intolerable back pain. We performed a logistic regression model in which surgical treatment was set as an objective variable, and other related factors including sex, age, the level of affected vertebrae, the quality of paralysis, changing rate (δ) of spinal canal encroachment, local kyphotic angle, mobility of collapsed vertebrae, EuroQol questionnaires (EQ5D), numerical rating scale (NRS), and Frankel grade as explanatory variables. We also plotted receiver operating curves (ROCs) to investigate the cutoff values of parameters at the baseline. Thirty patients (6 males and 24 females, mean age 76.7 years) were enrolled. Eventually 12 out of 30 patients avoided surgical treatment because their symptoms were improved. Logistic regression showed that δ of local kyphotic angle (odds ratio: 1.072), P = .01), mobility of collapsed vertebrae (1.063, 0.01), EQ5D (0.98, 0.04), and NRS (1.113, 0.01) were significantly correlated with the need for surgical treatments. Among the factors at baseline, only the mobility of collapsed vertebrae showed a significant value of area under a curve (AUC = 0.727, P = .008). The results that 40% of patients with ODVC did not need further surgical treatment after the intensive conservative treatment was of great significance. Patients with greater mobility of collapsed vertebrae might be treated surgically as quickly as possible.